Perancangan Interior Lobby, Lounge, Restaurant, dan Bar di Royal Avila Resort Malimbu, Lombok - Anastasia Gabby Chandra; Stephanus P Honggowidjaja (Intra, 2015)
Tourism has become very important and impactful nowadays. It takes important role in recreation terms. Recreation itself has become human secondary needs. Lombok is one of the best tourism spots in Indonesia. But the number of facilities and accommodations especially resort hotel are very low. Whilst resort hotel could become very appealing to people and easily become another beautiful tourism attraction. To answer that problem, we design Royal Avila Resort with lobby, lounge, restaurant and bar as its facilities. We hope that this design can create a comfortable hotel facility. Also we combine modern design and local traditional culture (Sasak) to make itself full with values. Technical values, humanity, symbolic, economic, and commercial value are some of the values it serves.